"Smart" Surface Capsules for Delivery Devices. Issue 6 (29th July 2014) - Skorb, Ekaterina V.; Möhwald, Helmuth
<x xml:space="preserve">Abstract</x> This review describes emerging trends, basic principles, applications, and future challenges for designing next generation responsive "smart" surface capsules. Advances and importance of "surface" capsules which are not deposited onto the surface but are built into the surface are highlighted for selective applications with specific examples of surface sponge structures formed by high intensity ultrasonic surface treatment (HIUS). Surface capsules can be adapted for biomedical applications, membrane materials, lab‐on‐chip, organ‐on‐chip, and for template synthesis. They provide attractive self‐healing anticorrosion and antifouling prospects. Nowadays delivery systems are built from inorganic, organic, hybrid, biological materials to deliver various drugs from low molecular weight substances to large protein molecules and even live cells. It is important that capsules are designed to have time prolonged release features. Available stimuli to control capsule opening are physical, chemical and biological ones. Understanding the underlying mechanisms of capsule opening by different stimuli is essential for developing new methods of encapsulation, release, and targeting. Development of "smart" surface capsules is preferable to respond to multiple stimuli. More and more often a new generation of "smart" capsules is designed by a bio‐inspired approach.